IMPLEMENTATION OF QUANTUM TEACHING MODEL TO INCREASE MATHEMATICAL COMMUNICATION SKILLS OF FIFTH GRADE PRIMARY SCHOOL STUDENT - HAYAT, OSEP SAEPUL (2015)
This research is held in one of primary school near Coblong area, Bandung city. This research aims to determine learning activity process and increase student mathematical communication skills by implementing quantum teaching for fifth grade student in primary school. Themethod used in this research is classroom action research adapting Kemmis and Mc Taggart design. This researchwas conducted in two meetings. Data collection technique was taken from students and observation result, field notes, and documentation. Subject of this research was 20 students of fifth grade primary school. The background of this research is student mathematical communication skills is still low. This can be seen during learning process when student showed difficulty of communicating their ideas both verbal and writing in mathematical skills. The average value pre-cycle reach 62,05 and showed there are 17 students below the average value. The results indicate by implementing quantum teaching showed a positive influence in student attitude and skill during learning activity. Cycle I students tend to be more inactive during learning process while in cycle II the instruction and learning activities are more active and joyful. This can be seen from mathematical communication evaluation result in cycle I reach average value74,34 with classical completeness teaching percentage reach 75%. In cycle II students average value increased and reach 83,33 with 94,44% student passed classical completeness teaching (KKM). Based on the research result we can concluded by implementing quantum teaching model can increased student mathematical communication skills. Learning process become more joyful and motivate student to learn. Researcher recommend to all relevant parties that implementation of quantum teaching is really helpful in increasing learning quality. Key words: quantum teaching model, student mathematical communication skills